Biochemical and biological characterization of ecuadorian pitviper venoms (genera Bothriechis, Bothriopsis, Bothrops and Lachesis) - Kuch, Ulrich (1996)
The lethality and enzymatic activities of venoms from six Ecuadorian pitvipers (Bothriechis schlegelii, Bothriopsis punctata, Bothriopsis taeniata, Bothrops asper, Bothrops atrox and Lachesis muta) are similar to those of other South and Central American species, but with a few exceptions: Bothriopsis taeniata venom had no coagulant activity, and Bothriechis schlegelii venom had no haemorrhagic activity.